Identity Politics & Power Relations Against Sexual Violence in Religious Higher Education Environment - Andreian Yusup; Siti Komariah; Siti Nurbayani K (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze how identity politics and power relations related to sexual violence in a religious campus environment. The research approach used was qualitative with a phenomenological method that can analyze the problem of sexual violence by analyzing the theory of hegemony and power relations. The informants for this study were campus officials, namely the Chancellor and his staff, the sexual violence task force and active university students with data collection techniques through observation, documentation, in-depth interviews, and literature studies, then analyzed descriptively and using source triangulation techniques. This study's results showed that identity politics and power relations influence sexual violence in the campus environment. This study concludes that the problem of sexual violence by perpetrators and victims in the campus environment can happen to anyone based on identity politics. This research implies that the higher education environment should be aware of social issues, especially sexual violence caused by identity politics and power relations.